Hydroxychloroquine in fighting COVID-19 : What led WHO to suspend clinical trial of drug? - Pacheco, Thyago José Arruda (2020)
Purpose: On March 11, 2020 the pandemic status of COVID-19 (Coronavirus Disease 2019) was declared. The milestone of thousands of daily deaths from Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was reached worldwide. So far, there is still no proven effective treatment against this disease. This study summarizes the main clinical findings on the use of hydroxychloroquine (HCQ) to treat COVID-19. The goal is to gather the evidence that led WHO to suspend the HCQ arm of its Solidarity Trial, contributing to the understanding of its denouement. Methods: LitCovid platform was searched for the term "hydroxychloroquine” in the “treatment” field. All clinical studies published in the period from January 1st to June 17th were included in the review. Results: We included ten articles on HCQ in COVID-19 positive patients (eight non-randomized and two randomized clinical studies). Most studies did not report a benefit in the use of HCQ. There is no evidence of decreased risk of intubation or death, and in some cases adverse effects have been reported, such as abnormal liver function, transient blurred vision, diarrhea. Conclusions: The overview of the available data on HCQ in COVID-19 patients can guide future studies, still needed to support public policies and health authorities in fighting COVID-19.